A Pocket Assay Grouting Technology for Rock Burst Control under Huge-Thick Conglomerate. (29th October 2020) - Shi, Junwei; Meng, Xiangrui; Du, Jifang; Dong, Yu; Wang, Ying
Abstract : As the carrier of force and energy, large-scale breaking or bending of huge-thick conglomerate tends to induce impact ground pressure in stope and tunnel. The stratum movement under huge-thick conglomerate was studied in this paper, which is mainly based on the key stratum theory for ground control. Based on this theory, the huge-thick conglomerate can be regarded as the main key stratum, and stratum movement or the development of grassroots state under huge-thick conglomerate will affect the structure itself, which may induce rock burst in stope and tunnel. The grouting technology is proved to effectively limit the bending settlement of conglomerate, control stress concentration of conglomerate, and improve the structure of the source of rock burst, which is an effective method for the control of huge-thick conglomerate. In this paper, the optimization of grouting filling material ratio is studied by the orthogonal experiments and the results show that the optimization of material ratio is cement: fly ash: gangue 1 : 2.22 : 4.44, concentration 75%. Under such conditions, pumpability and intensity reach the best. Meanwhile, a new technology, called pocket assay grouting technology, is put forward in this paper. It can prevent slurry leakage, protect the environment, and improve the efficiency of slip casting. The application of this technology in Huafeng mine shows that it not only realizes the safe, efficient, and green of coal mine but also provides technical support to control occurrence of rock burst induced by the movement of the huge-thick conglomerate in deep mining.